The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/nop2.251
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration and Satisfaction About Care Decisions in Team questionnaire—Psychometric testing of the Norwegian version, and hospital healthcare personnel perceptions across hospital units

Abstract: Aim To translate “The Collaboration and Satisfaction About Care Decisions in Team” questionnaire (CSACD‐T) into Norwegian and test it for psychometric properties. The further aim was to describe and compare healthcare personnel's collaboration and satisfaction about team decision‐making (TDM) across hospital units. Design A cross‐sectional study. Methods The questionnaire was translated into Norwegian. A total of 247 healthcare personnel at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The single item "Number of Events Reported", which indicates the number of adverse events the participants have reported over the past 12 months, has six response options: 1 = No events, 2 = 1 to 2 events, 3 = 3 to 5 events, 4 = 6 to 10 events, 5 = 11 to 20 events, 6 = 21 events or more [47]. All three questionnaires were translated into Norwegian and psychometrically tested [49][50][51]. In addition to the questionnaires, participants' background information was solicited (sex, age group, profession group, and employee time in the unit).…”
Section: Measurementsmentioning
confidence: 99%
“…The single item "Number of Events Reported", which indicates the number of adverse events the participants have reported over the past 12 months, has six response options: 1 = No events, 2 = 1 to 2 events, 3 = 3 to 5 events, 4 = 6 to 10 events, 5 = 11 to 20 events, 6 = 21 events or more [47]. All three questionnaires were translated into Norwegian and psychometrically tested [49][50][51]. In addition to the questionnaires, participants' background information was solicited (sex, age group, profession group, and employee time in the unit).…”
Section: Measurementsmentioning
confidence: 99%
“…To allow patients to participate in decisions regarding medical treatment, it is important to inform them about the possible risks and side effects. In a study of collaboration between physicians and nurses, the item ‘patient participation in decision-making’ had the lowest score in medical/surgical wards ( Aaberg et al, 2019a ). On the other hand, another study found that the staff and especially the physicians in surgical care considered information to be the most important for patient involvement ( Andersson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…All three questionnaires were translated into Norwegian and psychometrically tested [46][47][48]. In addition to the questionnaires, participants' background information was asked for (sex, age group, profession group, employee time in the unit).…”
Section: Phase 2 Make It Happen -Training Planning and Implementationmentioning
confidence: 99%